ANALISIS EVALUASI KINERJA PEMBANGUNAN PERIKANAN BUDIDAYA DI KOTA SAMARINDA - Hardin, Aisna; Fitriyana; Bambang Indratno Gunawan (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2022)
The purpose of this study is to formulate a policy strategy for aquaculture development in Samarinda City with SWOT analysis, and examine the main problems in the development of aquaculture in Samarinda City. The research was conducted from October 2021 to May 2022 in Samarinda City. Sample as many as 3 informants and 12 respondents with reference to the purpopsiv sampling method. The results showed that the strategy of the Samarinda City Fisheries Office is improve empowerment and coaching to farmers, utilize supporting infrastructure to strengthen Samarinda City as the center of the fishery products market, utilizing the existence of BBI as a technical implementer of hatchery and fish farming, utilizing marketing technonology support to meet the needs of fish in the community. The main problems of aquaculture development in Samarinda City are that aquaculture land was getting narrower, water quality was decreasing, feed prices were expensive and the lack of budget during the Covid-19 pandemic.The solutions carried out are urban-based cultivation, providing education to the community, utilizing independent feed and managing the use of budgets properly.